Transmisi Malaria Dari Penduduk yang Bermigrasi Ke Daerah Endemik Rendah - Malasari, Risma; Rahma, Nur; Rustam, Sri Nur Rahmi Nur; Sjahril, Rizalinda; Wahid, Isra (Majalah Kedokteran Indonesia, 2022)
Introduction: Malaria is an infectious disease that continues to be a public health issue worldwide, including in Indonesia. This study aims to detect the presence of Plasmodium parasites among immigrants from malaria endemic areas. Method: The research was conducted from September until November 2019 in three regency/cities in South Sulawesi, namely Makassar City, Tana Toraja and North Toraja. The population in this study were immigrants from malaria endemic areas (native Papua and non-Papua) who lived in the area for at least 2 years before visiting the cities of Makassar, Tana Toraja, or North Toraja. All samples were examined for malaria parasites using Polymerase Chain Reaction (PCR). Results: The results of the PCR test on 256 samples of migrants (native Papuan and non-Papuan) detected 19.53% positive for malaria. This research showed that a high prevalence of malaria parasites was found among asymptomatic immigrants, both native Papuans and non-Papuans in South Sulawesi. Conclusion: It can be concluded that the asymptomatic immigrants from endemic areas such as Papua need to be screened early because they may still have malaria parasites in their blood and become carriers, leading potential to cause local transmission.